Hydration of human and bovine serum albumin complexes with chlorophyllin investigated by differential ehf dielectrometry - Pesina, D. A.; Kashpur, V. A.; Khorunzhaya, O. V.; Shestopalova, A. V. (Biophysical Bulletin)
This study is designed to examine the hydration effects accompanying the interaction between chlorophyllin (CHLN), a potent inhibitor of experimental carcinogenesis, and human and bovine serum albumins (HSA and BSA) in aqueous solutions using differential dielectric method. This method allows studying both dielectric characteristics and hydration of the compounds under investigation. We show that for both complexes the process of complex formation is accompanied by changes of dielectric parameters. We also present calculations of the hydration of proteins and their complexes with ligand, which were carried out basing on the model concepts. We found that formation of CHLN complex with fatty acids free BSA is accompanied by a significant decrease of hydration while no notable hydration changes takes place upon formation of CHLN complex with HSA containing fatty acids. The former effect indicates that redistribution of free and bound water molecules takes place during the formation of the complex. The possible causes of effects observed are discussed.